CORRUPTION CRIME IN THE CRIMINAL EXECUTIVE SYSTEM OF THE RUSSIAN FEDERATION AND ITS PREVENTION - Sergey Girko, S.V. Kharchenko, S.U. Latyshev (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
the article analyzes determining corruption crime factors in the penal system of the Russian Federation through the analysis prism of the UN and Russian anti-corruption legislation, provides statistical information on corruption manifestations in the Russian Federation, presents the shortcomings of the legal regulation of factors aimed at combating corruption behavior in the penitentiary system